Design, analysis and development of new buck-boost and reduced EMI power conversion technology - Loh, Andrew Poh Chiang. (2008)
The newly proposed Z-Source inverter has been proven in the literature to exhibit both steady-state voltage buck and boost capabilities using a unique LC impedance network coupled between the power source and converter circuit. This paper now presents transient modeling and analysis of a voltage-type /.-source inverter. These aspects are found to be challenging and they need to be carefully investigated before attempting to design advanced control algorithms for controlling the /.-source inverter. Through detailed analysis, the paper identifies several phenomena on the dc and ac-sides of the inverter, which would result in the inverter having an inferior non-minimum-phase transient response. The dc-side phenomenon is associated with the Zrsource impedance network, which is shown through small-signal and signal-flow-graph analyses to be having a right-half-plane zero in its control-to-output transfer function. Also, the ac-side phenomenon is shown through space vector analysis to depend on the time intervals of inverter states used for reconstructing the desired inverter output voltage. Based on the ac vectorial analysis, a method for improving the inverter transient response is also presented. Lastly, simulation results obtained using a switching-functional model and experimental results obtained using a laboratory prototype are presented for validating the described theoretical concepts.